Swine hemoplasmosis detected in farms of Argentina by a new nested PCR assay - Pintos, M. E.; Posik, D. M.; Bonzo, E.; Perfumo, C. J.; Arauz, M. S. (Revista Veterinaria, 2021)
Swine hemoplasmosis or swine infectious anemia is a worldwide distribution disease caused by the hemotropic mycoplasmas Mycoplasma suis and Mycoplasma parvum. The aim of this study was to determine the presence of M. suis-M. parvum infection in subclinical pigs from herds of Buenos Aires province, Argentina, by means of new nested PCR. The PCR assay primers were designed based on the 16S ribosomal gene sequences of swine hemoplasmas available at GenBank. To standardize the assay, pig blood samples positive for hemoplasma by May Grünwald-Giemsa (MGG) stained blood smears were used. A total of 482 pig blood samples were analyzed. A 32% (154/482) of MGG stained blood smears were positive to M. suis o M. parvum. From these 154 samples, 47% (72/154) were positive by PCR. Sequences of PCR products amplified with these primers always showed identity with M. suisor M. parvum, validating their specificity and highlighting the unspecific amplification with hemoplasmas of other species. This is the first assay designed in Argentina to identify M. suis and M. parvum. However, considering the advances in the knowledge of the genome of hemoplasmas worldwide, further studies should be performed to standardize new assays for the diagnosis of swine hemoplasmosis in Argentina.